Reproductive biology of the spotted scat Scatophagus argus (Linnaeus, 1766) from Mandapam waters, south-east coast of India - Gandhi, V.; Venkatesan, V.; Ramamoorthy, N. (Indian Journal of Fisheries, 2014)
Reproductive biology of the spotted scat Scatophagus argus (Linnaeus, 1766) was studied by examining 1,659 individuals collected fortnightly between August 1995 and July 1997 from the Gulf of Mannar along Mandapam coast. Overall sex ratio (1:2.2) indicated that the population had significantly higher proportion of females than males (Ï‡2 test, p